KEADILAN GENDER DALAM PERAN PEKERJA PEREMPUAN DI PT DJARUM KUDUS PERSPEKTIF AMINA WADUD - Fiza Umi Latifah (Qolamuna : Jurnal Studi Islam, 2025)
This research aims to analyze the manifestations of gender injustice experienced by female workers at PT Djarum Kudus using Amina Wadud's hermeneutic perspective of gender justice. As a pillar of the tobacco products industry, female workers in the hand-rolled clove cigarette (SKT) segment often face vulnerable working conditions despite their vital role. This research uses a qualitative method with a library research approach, analyzing secondary data from relevant journals, theses, and reports. Data analysis was conducted through critical content analysis and hermeneutic methods, where empirical data on workers' conditions were interpreted through Amina Wadud's theoretical framework. The results identified four forms of systemic gender injustice: (1)Stereotypes that label women as “diligent, conscientious, obedient, and cheap” workers; (2) Subordination that places them in unskilled jobs; (3) Economic marginalization through a piece-rate system that creates income uncertainty and wage gaps; and (4) Double burden between factory work and domestic responsibilities. Analysis from Wadud's perspective shows that these practices are a violation of fundamental theological principles. Subordination denies women's status as equal khalifahs (moral agents of God), economic marginalization contradicts the Qur'anic principle of justice ('adl), and the double burden is a product of patriarchal socialconstruction, not divine nature. In conclusion, Amina Wadud's hermeneutics reframes the struggle of women workers not only as a secular demand for rights, but as a theological struggle to realize justice and human dignity inherent in Islamic teachings. Keywords: Gender Justice, Women Workers, Amina Wadud